VIRTUAL EFFECTIVENESS OF REPRODUCTIVE HEALTH EDUCATION FOR VIRTUAL CHILDREN IN THE AKB ERA AT KOTA BOGOR - Fitria, Dedes; Nurhayati, Titi (Universitas Pendidikan Indonesia (UPI), 2022)
Knowledge of reproductive health is very important to limit sexual behavior that is increasingly free in adolescence, especially during early adolescence. A study in Cameroon showed that women with disabilities have limited understanding of reproductive health and have low reproductive health education.Health education delivered can use a variety of media including modules in the form of print, audio and video. Rosaria's research stated that there was a significant difference in the intervention group that received socialization on the HIV/AIDS prevention module and had better knowledge and attitudes than the control group. The preliminary study at SLB S found that most of the students at the special school did not know about the importance of knowing about adolescent reproductive health because they had never received education about reproductive health. So the authors were interested in conducting a study on the effectiveness of virtual reproductive health education for blind children in the AKB era in Bogor cityThis study aims to determine the success of the Effectiveness of Reproductive Health Virtual Education for Blind Children in the AKB Era in Bogor City. The research design used in this study was a quantitative method using a quasi-experimental form of nonrandomized control group pretest-posttest design taking place in the city of Bogor. Quantitative data analysis included univariate and multivariate analysis using parametric test Unpaired T test with alternative nonparametric Mann-Whitney test.The results of the study show that the use of virtual modules is effective in increasing knowledge and attitudes for children with visual impairments with a p-value 000.5. Suggestion. The use of virtual educational modules can be used as interesting and simple educational media in providing health education to adolescents, especially children with visual impairments.